Recent Applications of Azo Dyes: A Paradigm Shift from Medicinal Chemistry to Biomedical Sciences - Khan, Md. N.; Parmar, Digvijaysinh K.; Das, Debasis (Mini Reviews in Medicinal Chemistry, 2021)
Azo molecules possess the characteristic azo bond (-N=N-) and are considered fascinating motifs in organic chemistry. Since the last century, these brightly colored compounds have been widely employed as dyes across several industries in applications for printing, food, paper, cosmetics, lasers, electronics, optics, material sciences, etc. The discovery of Prontosil, an antibacterial drug, propelled azo compounds into the limelight in the field of medicinal chemistry. Subsequent discoveries including Phenazopyridine, Basalazide, and Sulfasalazine enabled azo compounds to occupy a significant role in the drug market. Furthermore, azo compounds have been employed as antibacterial, antimalarial, antifungal, antioxidant, as well as antiviral agents. The metabolic degradation of many azo dyes can induce liver problems if ingested, posing a safety concern and limiting their application as azo dyes in medicinal chemistry. However, azo dyes remain particularly significant for applications in cancer chemotherapy. Recently, a paradigm shift has been observed in the use of azo dyes: from medicinal chemistry to biomedical sciences. The latter benefits from azo dye application are related to imaging, drug delivery, photo-pharmacology and photo switching. Herein, we have compiled and discussed recent works on azo dye compounds obtained so far, focusing on their medicinal importance and future prospects.
Keywords: antibacterial